Pattern of Antimicrobial Resistance among Bacterial Isolates from Urogenital Clinical Specimens: A Descriptive Study from the Buea Health District, Cameroon - Amin, Elvis Tajoache (Drugs Real World Outcomes, 2018)
INTRODUCTION: Antimicrobial resistance has become a global concern and is particularly affecting developing countries where infectious diseases and poverty are endemic. The effectiveness of currently available antimicrobials is decreasing as a result of increasing resistant strains among clinical isolates. OBJECTIVES: The aim of this study was to determine the resistance pattern of bacterial isolates from different clinical urogenital specimens at different hospitals in the Buea Health District, Cameroon. METHODS: A retrospective study was conducted in three hospital laboratories in the Buea Health District, Cameroon, from June to August 2017. All culture and antimicrobial susceptibility test results of patients who presented at each of the laboratories for urine, vaginal swab or urethral swab cultures from January 2012 to December 2016 were included in the study. Data were analysed using SPSS Windows version 20.0. The comparisons between different isolates’ resistance to antimicrobials were performed using the chi-square test. The difference in the resistance of urogenital isolates to various antimicrobials within different years was also compared by the chi-square test. RESULTS: A total of 423 bacterial isolates were obtained from clinical urogenital specimens such as: urine 93 (21.9%), vaginal swab 175 (41.4%) and urethral swab cultures 155 (36.6%). The predominant bacterial isolates were Staphylococcus spp. 320 (75.5%), Escherichia coli 37 (8.7%) and Enterococcus spp. 24 (5.7%). All the isolates showed significantly high resistance rates to amoxicillin/clavulanic acid (67.6% resistant rate, p = 0.025), but most isolates, except those of Staphylococcus, were relatively more susceptible to nitrofurantoin (82.6% susceptibility rate, p = 0.045). However, Staphylococcus spp. was more susceptible to ceftriaxone (91.0% susceptibility rate, p < 0.0001) and cefotaxime (74.4% susceptibility rate, p = 0.034). Generally, most of the isolates showed significantly rising rates of resistance to the majority of the antimicrobials tested from 2012 to 2017. CONCLUSION: Our findings showed a progressively rising rate of antimicrobial resistance in urogenital bacterial isolates over the last 5 years in the Buea Health District. Thus, uncontrolled and irrational use or prescription of these drugs should be avoided to maintain low resistance of highly susceptible antimicrobials.